Urban to forest gradients: Suitability for hollow bearing trees and implications for obligate hollow nesters. (3rd July 2014) - Isaac, Bronwyn; White, John; Ierodiaconou, Daniel; Cooke, Raylene
Abstract Resource availability is a limiting factor influencing the distribution and composition of faunal communities. Globally, hollow bearing trees are a resource required by wildlife at all trophic levels, and are used for a diverse range of ecological functions. In the northern hemisphere avian species act as primary hollow excavators, whereas the southern hemisphere must rely on complex interactions between stochastic events, and eventual decay. Hollow formation is therefore a slow process in the southern hemisphere. In contrast, hollow loss is quite rapid and influenced greatly by anthropogenic impacts. To identify the ecological characteristics driving hollows over an urban to forest gradient as a resource for the powerful owl (Ninox strenua) and its prey we used presence‐only modelling. The potential for an area to support tree hollows suitable for powerful owls and their prey was linked to the density of ephemeral rivers, land cover, tree cover and distance from riparian vegetation. The potential for large hollows throughout the landscape, suitable for the powerful owl, was also influenced by density of permanent rivers. Potential habitat for tree hollows, capable of supporting powerful owls and their prey was greatest in forested environments, declining with increased urbanization. However the urban region still supported some smaller tree hollows suitable for arboreal marsupials. Managing for urban dwelling species, is not as simple as retaining old hollow producing trees or providing alternate nesting structures. We also need to mitigate increased mortality associated with built environments (e.g. electrocution, collisions).